Descriptive study of 192 adults with speech and language disturbances - Mansur, Letícia Lessa; Radanovic, Márcia; Rüegg, Danielle; Mendonça, Lúcia Iracema Zanotto de; Scaff, Milberto (São Paulo Medical Journal, 2002)
CONTEXT: Aphasia is a very disabling condition caused by neurological diseases. In Brazil, we have little data on the profile of aphasics treated in rehabilitation centers. OBJECTIVE: To present a descriptive study of 192 patients, providing a reference sample of speech and language disturbances among Brazilians. DESIGN: Retrospective study. SETTING: Speech Pathology Unit linked to the Neurology Division of the Hospital das Clínicas of the Faculdade de Medicina da Universidade de São Paulo. SAMPLE: All patients (192) referred to our Speech Pathology service from 1995 to 2000. PROCEDURES: We collected data relating to demographic variables, etiology, language evaluation (functional evaluation, Boston Diagnostic Aphasia Examination, Boston Naming and Token Test), and neuroimaging studies. MAIN MEASUREMENTS: The results obtained in language tests and the clinical and neuroimaging data were organized and classified. Seventy aphasics were chosen for constructing a profile. Fourteen subjects with left single-lobe dysfunction were analyzed in detail. Seventeen aphasics were compared with 17 normal subjects, all performing the Token Test. RESULTS: One hundred subjects (52%) were men and 92 (48%) women. Their education varied from 0 to 16 years (average: 6.5; standard deviation: 4.53). We identified the lesion sites in 104 patients: 89% in the left hemisphere and 58% due to stroke. The incidence of aphasia was 70%; dysarthria and apraxia, 6%; functional alterations in communication, 17%; and 7% were normal. Statistically significant differences appeared when comparing the subgroup to controls in the Token Test. CONCLUSIONS: We believe that this sample contributes to a better understanding of neurological patients with speech and language disturbances and may be useful as a reference for health professionals involved in the rehabilitation of such disorders.